Precautionary savings and wealth inequality: A global sensitivity analysis - Marco Cozzi (Queen's University, Department of Economics, 2011)
This paper applies Canova JAE 1994 methodology to perform a thorough sensitivity analysis for the Aiyagari QJE 1994 economy. This is a calibrated GE model with incomplete markets and uninsurable income risk, designed to quantify the size of precautionary savings and the degree of wealth inequality. The results of this global robustness analysis are broadly consistent with Aiyagari's findings. Even when considering priors for the parameters uncertainty which are highly dispersed, the size of the precautionary savings is modest: at most, they account for an 11% increase in the saving rate. However, the results show that the parameter representing the exogenous borrowing limit seems to lead to relatively large changes in measures of wealth inequality. The Gini index increases by 15 points when considering values of the borrowing limits that lead to empirically plausible shares of households with a negative net worth. The parameters that quantitatively have the largest effects on determining the wealth Gini index are the capital share, the borrowing limit, and the depreciation rate. The parameters affecting most significantly precautionary savings are the risk aversion and the standard deviation of the income shocks.
Keywords: D52; D58; E21; 330; Precautionary Savings; Calibration; Heterogeneous Agents; Incomplete Markets; Computable General Equilibrium; Monte Carlo; Vermögensverteilung; Soziale Ungleichheit; Sparen; Unvollkommener Markt; Risikoaversion; Sensitivitätsanalyse; CGE-Modelling